A Sharpe-ratio-based measure for currencies - Javier Prado-Dominguez; Carlos Fernańdez-Herraíz (European Journal of Government and Economics (EJGE), 2015)
The Sharpe Ratio offers an excellent summary of the excess return required per unit of risk invested. This work presents an adaptation of the ex-ante Sharpe Ratio for currencies where we consider a random walk approach for the currency behavior and implied volatility as a proxy for market expectations of future realized volatility. The outcome of the proposed measure seems to gauge some information on the expected required return attached to the "peso problem".
Keywords: 330; Sharpe Ratio; peso problem; carry trade; currency strategies.